Authenticity Identification of Meat Products Using Multienzyme Isothermal Rapid Amplification-Lateral Flow Dipstick - SHANG Ke, ZHANG Biao, ZHANG min, YANG Huayu, YE Mei, DUAN Qingzi, WANG Wei, GONG Yajun (Shipin Kexue, 2024)
Purpose: To address the issue that laboratory methods cannot meet the need foron-site rapid testingat the grassroot level, a quick method for detecting the authenticity of meat products was established based on multienzyme isothermal rapid amplification (MIRA) coupled with lateral flow dipstick (LFD). Methods: Pig, cattle, sheep, chicken, and duck-specific mitochondrial gene sequences were selected through GenBank, and intra-species conserved and inter-species specific target fragments were compared using the DNAStar Megalign software. According to the design principles of MIRA primers and probes, target gene-specific primer and probe sets were designed and screened systematically through positive, negative and blank controls to determine the species-specific primers and probes. The reaction system, temperature, and time were optimized. Analytical figures of merit of the method including DNA extraction, sensitivity, detection limit, false positive rate and false negative rate were evaluated to verify its validity. Results: Compared with real-time fluorescent polymerase chain reaction (PCR), the average false positive rate of this method was 3.49%, and the false negative rate was 3.54%, which meets the requirements of on-site rapid testing. Conclusion: In this study, the MIRA-LFD technique was established for 5 common meats, namely, cattle, sheep, pig, chicken and duck, and its validity and feasibility were confirmed, realizing on-site rapid testing of the authenticity of meat products.